2009
DOI: 10.1002/jssc.200900304
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl caffeate from Verdicchio wine: Chromatographic purification and in vivo evaluation of its antifibrotic activity

Abstract: Ethyl caffeate (CfE, caffeic acid ethyl ester) was extracted from dealcoholized Verdicchio, a white wine from Marche (Italy) with ethyl acetate and then purified with semipreparative reversed-phase high-performance liquid chromatography (RP-HPLC) using an ODS2 column (25 cm  20 mm id) at an isocratic flow of 5 mL/min (the mobile phase A was formic acid 4.5% in water and the mobile phase B was acetonitrile). The CfE extract administered intraperitoneally at 1 mmol/L in rats previously treated with 10 mg/kg dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Caftaric, cis and trans-coutaric acid and fertaric are the cinnamic acids formed in the grape berries from the esterification of caffeic, coumaric and ferulic acid with tartaric acid, respectively. Verdicchio has been already reported as a good source of these congeners in previous work (Boselli et al, 2009). Since all the phenolic compounds are prone to oxidation, GSH can react with the quinonic form of the cinnamic acids through an electrophilic addition leading to the regeneration of the cinnamic form.…”
Section: Phenolic Profilementioning
confidence: 98%
See 1 more Smart Citation
“…Caftaric, cis and trans-coutaric acid and fertaric are the cinnamic acids formed in the grape berries from the esterification of caffeic, coumaric and ferulic acid with tartaric acid, respectively. Verdicchio has been already reported as a good source of these congeners in previous work (Boselli et al, 2009). Since all the phenolic compounds are prone to oxidation, GSH can react with the quinonic form of the cinnamic acids through an electrophilic addition leading to the regeneration of the cinnamic form.…”
Section: Phenolic Profilementioning
confidence: 98%
“…This compound is more lipophilic than the free form of caffeic acid (and presumably more readily absorbed by cell membranes), thus, its bioavailability is expected to be higher than non esterified phenolics such as anthocyanins or catechins. Boselli, Bendia, Di Lecce, Benedetti, and Frega (2009) have also demonstrated that CfE extracted from Verdicchio wine may exert hepatoprotective and antifibrotic effects by acting both at the cellular and molecular level in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 94%
“…Caffeic acid is considered a strong antioxidant against LDL oxidation, so it contributes to the beneficial health effects of wines (Meyer, Donovan, Pearson, Waterhouse, & Frankel, 1998). Recent experimental work has evidenced that flavonols, hydroxycinnamates and their ethyl esters (Boselli, Bendia, Di Lecce, Benedetti, & Frega, 2009) are directly correlated to the antioxidant capacity of white wines (Hernanz et al, 2007;Makris et al, 2003). The knowledge accumulated so far suggests that phenols also elicit an array of biological activities, which may be associated with a depressed rate of degenerative processes (Darias-Martín et al, 2004;Fuhrman, Volkova, Suraski, & Aviram, 2001;Nardin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The biological effects of L. fischeri are derived from EC. EC is known to exhibit anticancer [8], anti-inflammatory [9], and antifibrotic activities [10]. In addition, it has the potential to regulate blood pressure by inhibiting aldosterone synthase [11].…”
Section: Introductionmentioning
confidence: 99%